Gestión administrativa – financiera y su incidencia en la productividad, de los programas de Agricultores Pronaca zona Balzar, Periodo 2013 - 2014. Manual de procesos operativos. - Pincay Abril, Flor Gisella (2016)
The National food processing company C.A. PRONACA, is from Ecuador is aimed at providing confidence and acceptance within and outside the country. Founded in 1957 where he was born as India coming to strengthen the agricultural field research and seed production in the area Balzar in one of his haciendas La Josefina located at Km 15 via Balzar - El Empalme. This research aims to evaluate the incidence of administrative - financial in the level of productivity programs in the area Balzar Pronaca farmers. The methods used in this study were descriptive statistical and purposeful; and the techniques used were: surveys and interviews, the sample was 218 farmers. The results determined that 8% of farmers surveyed belong to the PPC program, while 92% are in the group of PII, where 54% of them grow maize using between 10 to 12 average has. 100% of farmers acquire agricultural inputs on credit to the company and 67% of them have obtained a production ranges between 450 to 1,000 qq qq; for controlling planting 50% of respondents say they frequently receive technical assistance biweekly. Such test results allow the hypothesis: "Inadequate administrative management - financial adversely affects the level of productivity of farmers Balzar area programs". At the end of the investigation the proposal to develop a manual of operating processes of the Balzar area Pronaca farmers programs in order to regulate existing activities and establishing accountable in each area was raised